Morphometric characteristics of spiny-cheek crayfish Faxonius limosus (Rafinesque, 1817) from the Danube River on the territory of Serbia - Roljić, Rajko L.; Nikolić, Vera P.; Đikanović, Vesna Đ.; Zorić, Katarina S.; Urošević, Aleksandar M.; Marković, Vanja M. (Archives of Biological Sciences, 2024)
Paper description: The spiny cheek crayfish, Faxonius limosus, is one of the most invasive alien species in Europe. The first record in Serbia was reported 20 years ago. This research aimed to better describe the morphometric characteristics of this species in the Serbian part of the Danube River. F. limosus specimens were measured to describe their general body shape in more detail using linear and geometric morphometric methods. The presented results contribute to a better understanding of the invasive spiny cheek crayfish in the recipient habitat. Abstract: Twenty-three morphometric characteristics of spiny-cheek crayfish Faxonus limosus from Danube, Serbia, were analyzed to describe the general body shape. Forty-eight specimens were caught in May 2022 and January 2023 and measured for morphometric variation. Also, the values of two crayfish condition indices, Fulton’s condition factor (FCF) and crayfish constant (CC), were determined. Most of the analyzed characteristics were moderately variable (CV 10-30%). Principal component analysis (PCA) was applied to the morphological measurements. All the variables make similar contributions to the variance of the first principal component. The highest contributions are from variables CEF and ARL.ARW, CPH, ABH, CPW, and ROW significantly contributed to the second principal component variance. The population of spiny-cheek crayfish at the investigated site has a relatively stable age structure.